Impact of the COVID-19 pandemic on ovarian tissue cryopreservation planning in the Bologna clinical center - Magnani, Valentina; Vicenti, Rossella; Fabbri, Raffaella; Paradisi, Roberto; De Meis, Lucia; Raimondo, Diego; Casadio, Paolo; Seracchioli, Renato (Frontiers in Oncology, 2022)
Objective: The aim of the study was to evaluate the repercussions of the COVID-19 pandemic on the activity levels of ovarian tissue cryopreservation (OTC) in the our center. Methods: The study analyzed the number of patients treated for OTC in our center during three periods: pre-pandemic period: March 2019-February 2020, pandemic period: March 2020-February 2021 and post-pandemic period: March 2021-February 2022. Results: In our center routine hospital operation was completely reorganized, allowing only urgent interventions. Continuing to urgently preserve fertility during the pandemic required rapid changes to our standard practices for the care of these vulnerable patients. Despite the modifications, there was no difference in the number of OTC performed among the periods analyzed. Similarly, the number of patients who did not perform OTC was the same over the three years analyzed. Conclusions: Despite the local and national restructuring of care to conserve resources and protect the community, it is significant to continue offering fertility-sparing treatment to cancer patients. This emphasis on the importance of preserving fertility despite the pandemic further highlights the essential and urgent nature of this procedure.